EFIKASI CENDAWAN ENTOMOPATOGENIK UNTUK MENGENDALIKAN ULAT BULU - Prayogo, Yusmani; Marwoto, Marwoto; Suharsono, Suharsono (JURNAL BIOLOGI INDONESIA, 2012)
The efficacy of entomopthogenic fungus for Tussock Moth Caterpillars Control. The occurrence of Tussock Moth Caterpillar (TMC) out break reported in some areas in East Java at Probolinggo, Malang, Batu and other districts were worried. The high caterpillar population not only attacking mangos, cherry, and wild watercress, but also migrating to living house before pupation. The available control of these caterpillar is chemical pesticide. However, thechemical will kill the natural enemies and other beneficial insects. A laboratory experiment to study the efficacy of five entomopathogenic fungus against TMC and pupae was conducted at the Entomology Laboratory of Indonesian Legumes and Tuber Crops Research Institute (ILETRI) in April 2011. Our experiment was arranged using completely randomized design (CRD) with three replicates using five entomopthogenic fungus. The efficacy was determined by the mortality of caterpillar/larva and pupae infected by the fungus. Result showed that these five fungus had not effectively kill the caterpillar, as the dense setae in integument acted as a mechanical barrier to fungus infection. The pupal stage was more susceptible to fungus infection. It was found that Paecilomyces fumosoroseus and Lecanicillium lecanii fungus were more effective than Metarhizium anisopliae, Beauveria bassiana and Nomuraea rileyi repectively. These two fungus could kill 90% of pupae and also were easier to be cultured in a wide range of natural media. Therefore P. fumosoroseus and L. lecanii are potentially used as a biological control agent against TMC out break.Keywords: Entomopathogenic fungus, hairy caterpillar, incubation period, colonization